Chemical speciation of cadmium and lead and their bioavailability to cole (Brassica campestris L.) from multi-metals contaminated soil in northwestern China. Issue 1 (1st October 2016) - Yang, Yiming; Li, Yu; Zhang, Jihui
Abstract: A pot experiment was conducted to study the relationship between speciation distribution of cadmium (Cd) and lead (Pb) and their availability to cole ( Brassica campestris L.) grown on the Cd–Pb polluted soil in northwest of China. The results showed that Cd in the unpolluted soil was mainly bound to carbonate fraction (F2) and Fe–Mn oxide fraction (F3), and Pb was mainly bound to carbonate fraction (F2) and residual fraction (F5). However, marked change of Cd and Pb fractionation was observed with increasing soil Cd and Pb concentrations, where the concentrations of Cd in F1 (exchangeable fraction), F2 and F3 increased significantly ( p  < 0.001 for F1, F2 and F3), and Pb in F1, F2, F3 and F4 increased significantly ( p  < 0.001 for F1, F2, F3 and F4).The correlation analysis between the fraction distribution coefficient of Cd and Pb in the soil and Cd and Pb concentration accumulated in cole showed that both Cd and Pb in F1 fraction in the soil made the greatest contribution on the accumulation of Cd and Pb in cole. Higher bio-concentration factors (BCFs) and translocation factors (TFs) for Cd and lower BCFs and TFs for Pb were observed in the cole, respectively. Cd had higher accumulation in the edible parts of the cole, but Pb had lower accumulation in that. Therefore, Cd has higher risk to human health than Pb when people eat the coles grown in Cd–Pb polluted soil in northwestern China.